Animal model studies on viral infections - Tomoyuki Miura (Frontiers Research Topics, 2015)
Understanding viral replication and pathogenicity properties in infected individuals is a major mission of animal virology. Animal models are essential to analyze the in vivo viral characteristics and to develop countermeasures against viruses. To fight against a wide variety of viruses, basic studies with specific and/ or common approaches are required. This Research Topic collects articles that describe studies on numerous virus species at various stages toward animal experiments: (i) description/evaluation/ new challenges of animal model studies; (ii) experimental material/methods for animal model studies; (iii) observations for upcoming animal model studies. Numbers of DNA and RNA viruses such as HHV-6, HPV, Ebola virus, HCV, dengue virus, HTLV-1, HIV-1, SIV, and measles virus are covered by this special issue consisting of original research, methods, review, mini-review, and opinion articles. All readers would understand, we believe and hope, that animal model studies are critical for current virology as always.